Sugar, fat, or protein: are all food insecure households eating the same? The case of small rice producers in Peru - Useche, Pilar; Twyman, Jennifer (Emerald Publishing Limited, 2016)
Purpose _ We examine the joint demand for components of a household’s diet diversity and its relationship with household and regional characteristics that embody diverse food access and utilization constraints within the framework of the dietary patterns of rice producers in Peru. Methodology/approach _ We use multivariate probit regression to account for the simultaneous nature of the choice of different dietary group components. Findings _ here are diverse food intake patterns for households, depending on their wealth, education, demographic structure, market access and geographic location, as well as past shocks. There are also several obesogenic foods that are complements to consumption, with milk being a strong substitute for some of them. Of particular concern is the high vulnerability of female-headed households to low consumption of micronutrient-rich foods as well as the high vulnerability of households with children to high consumption of beverages with added sugars. Climate shocks are also highly associated with poor diet quality. Practical implications _ Results show the important influence of trade on household nutrition and food security. They indicate that policy and program recommendations should focus on nutrition information (such as labeling requirements) and education so that consumers can make informed decisions. They also suggest that policy makers should focus on how to make healthy foods available during crises to prevent health issues after economic and climatic shocks.